Comparison of spinal anaesthesia with isobaric chloroprocaine and general anaesthesia for short duration ambulatory urological procedures - Siddarth Ravi; Handattu M Krishna (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Chloroprocaine is a short-acting local anaesthetic agent for spinal anaesthesia (SA) that has been used in day care surgeries due to its faster recovery characteristics and faster discharge rates compared to other local anaesthetics. This study aimed at finding out its efficacy for the same as compared to general anaesthesia (GA). Material and Methods: This observational study was conducted on 60 patients belonging to the American Society of Anaesthesiologists (ASA) physical status I and II who underwent short elective urological procedures (<60 min) under GA (group GA) as per standard of care in our hospital (n = 30) and SA (group SA) with 50 mg 1% isobaric 2-Chloroprocaine (n = 30). Time taken to meet the discharge criteria, modified Aldrete score and modified post anaesthesia discharge score in each group were noted. The cost of the anaesthetic procedure, anaesthetic procedural time, hemodynamics, supplemental analgesia, complications related to the procedure were noted and compared. Results: Patient characteristics and duration of surgery were comparable. Time taken by group SA was significantly higher than group GA to meet the discharge criteria. Cost of GA [2624.76 (166.16) units] was significantly more than SA [1561.63 (81.32) units, P < 0.05]. There was no requirement of supplemental analgesia in group SA and no hemodynamic instability or complications in either group. Conclusion: GA is significantly better as compared to SA with 50 mg 1% isobaric 2-Chloroprocaine as an anesthetic technique in day care urology surgeries in terms of faster recovery and faster discharge rate but is costlier.